Pseudoangiomatous stromal hyperplasia of the breast: an unusual indication for mastectomy - Fonseca-Moutinho,José Alberto (2019)
Pseudoangiomatous Stromal Hyperplasia (PASH) is a benign proliferation of the mammary stromal tissue. We present a clinical case of a 74-years-old patient presenting a fast-growing PASH, treated through mastectomy, with no recurrence or breast cancer after a 11-years follow up. The patients clinical history, imaging, histopathologic examinations, treatment, and follow up were reviewed, along with 9 other cases described in literature. Considering that PASH is a condition that needs removal through an excision with safe margins, in case of fast-growing or large lesions, mastectomy seems to be a safe long-term treatment, with low risk of relapses or contralateral breast pathology.